Maurar í húsryki á íslenskum bóndabæjum - Gunnar Guðmundsson; Sigurður Þór Sigurðarson; Kristinn Tómasson; Davíð Gíslason; Hallas, Thorkill (Læknafélag Íslands, Læknafélag Reykjavíkur, 2008)
Neðst á síðunni er hægt að nálgast greinina í heild sinni með því að smella á hlekkinn View/Open BACKGROUND: Sensitization to Dermatophagoides pteronyssinus (D. pteronyssinus) occurs in 9% of the Reykjavik population, despite the fact that no Der p 1 antigen has been found in the area. A recent study revealed that sensitized persons more often had a childhood history of work or holiday stay in rural areas than controls. As a follow up we studied the risk of exposure to mites in farmland dwellings. METHODS: In a survey of work-related lung disorders among farmers in the south and west of Iceland, 80 samples of house dust, representing 42 farms, were collected from bedroom mattresses and the floors in living rooms and examined for mites. Treatment of samples was identical with the method used earlier in the Reykjavik investigation (ECRHS II). RESULTS: In contrast to the Reykjavik results, dust from farm dwellings showed a large diversity of mites. Seventeen taxons were found, with Acarus siro and D. pteronyssinus in 13 and 8 farms respectively, but the samples did not show signs that any of the taxons actually had lived or reproduced where they were collected. CONCLUSION: The finding of D. pteronyssinus in farmland dwellings provides a possible explanation of why some Reykjavik citizens might have developed sensitization to this mite, even though cross sensitization to other species of mites could give a false positive reaction to D. pteronyssinus in at least some of those cases. Our observations did not support the idea that the mites were living in the dwellings and an explanation for their occurrence must be sought in the outdoor environment. Bakgrunnur: Næming fyrir Dermatophagoides pteronyssinus (D. pteronyssinus) finnst hjá 9% Reykvíkinga þrátt fyrir að engir Der p 1 mótefnavakar hafi fundist á Reykjavíkursvæðinu. Nýleg rannsókn sýndi að næmir einstaklingar höfðu unnið eða dvalið í sveit á barnsaldri oftar en samanburðarhópur. Til að fylgja þessu eftir könnuðum við líkur á útsetningu fyrir maurum á ...